Manevi bakım verme ölçeği'nin hemşire grubunda güvenirlik ve geçerliği - Güzel, Ayşe (İstanbul Sabahattin Zaim Üniversitesi, Lisansüstü Eğitim Enstitüsü, Hemşirelik Anabilim Dalı, 2020)
Çalışmanın amacı Tiew ve Creedy (2012) tarafından geliştirilen, Çoban ve arkadaşlarının (2017) Türkçe uyarladıkları "Manevi Bakım Verme Ölçeği" (Spiritual Care-Giving Scale)'nin hemşire grubunda güvenirlik ve geçerliğinin incelenmesidir. Araştırma metodolojik olarak planlanmıştır. Araştırmanın örneklemini palyatif bakım merkezi, yoğun bakım ünitesi ve onkoloji servisinde çalışan 219 hemşire oluşturmuştur. Verilerin analizinde güvenirlik için Cronbach Alpha (α), Tabakalı Alpha Katsayıları, Madde-toplam puan korelasyonu ve Test-tekrar test korelasyonuna bakılmıştır. Geçerlik analizinde Doğrulayıcı faktör analizi (DFA) ile Benzeme ve Ayırma Geçerliği yöntemleri kullanılmıştır. Cronbach Alpha değerleri tüm boyutlar için kabul edilen değerin üzerinde bulunmuştur. Ölçeğin toplamına ait Cronbach α=.95 ölçeğin alt boyutları için α değerleri sırasıyla .89, .92, .88, .83, .72 olarak bulunmuştur. Tabakalı α katsayısı .99 olarak belirlenmiştir. Madde Toplam Puan Korelasyonları .402 ile .729 (p<0,001) arasında değerler almıştır. DFA 'da ölçek maddelerinin faktör yükleri arasında .40 ile .97 arasında, GFI>.92, RMSEA<.80 ve SRMR<.90 değerleri bulunmuştur. Benzeme geçerliği ne ilişkin analiz sonuçlarında standart regresyon ağırlıklarının (λ)>.50, yapı güvenirlik Katsayısının (ω)> .70 olması, bir faktörde açıklanan ortalama varyansın (AVE)> .50 ve (ω)>AVE'den büyük olduğu gözlenmiştir. Bu değerler benzeme geçerliğini sağladığını gösterir. Ayırma geçerliğinde ise tüm boyutlar için MSVAVE ve √AVE değerinin diğer faktörlerle korelasyonlarından büyük olduğu görülmektedir. Bu sonuçlarda bize ölçeğin ayırma geçerliğini kısmen sağladığını göstermektedir. Geçerliğe ilişkin yapılan tüm analizler sonucunda orijinal modele ilişkin beş faktörlü yapıyı doğruladığı, madde ve alt boyutların ölçekle ilişkili olduğu ve maddelerin bağlı olduğu alt boyutları yeterince açıkladığı görülmüştür. Araştırma sonucunda yapılan tüm analizlere göre "Manevi Bakım Verme Ölçeği" hemşire grubu için güvenilir ve geçerli bir ölçek olarak belirlenmiştir.

The aim of the study is to examine the validity and reliability of the Spiritual Care- Giving Scale, developed by Tiew and Creedy (2012), and adapted to Turkish by Çoban et al. (2017), in the nurse group. The study was planned methodologically. The sample of the study consisted of 219 nurses working at the palliative care centers, intensive care units and oncology clinics. Cronbach's Alpha (α), McDonald's Omega (ω), Layered Alpha Coefficients, Item-total Correlation and Test-retest Correlation have been used in the analysis of the data to provide the reliability of the data analysis. In validity analysis, Confirmatory Factor Analysis (CFA) and Similarity and Discriminant Validity (SDV) methods have been utilized. Cronbach's alpha values for validity were found to be above the acceptable value for all dimensions. Cronbach's alpha was found to be .95 for the total scale and .89, .92, .88, .83, and .72, respectively, for its sub-scales, respectively. Layered alpha coefficient was determined to be .99. The item-total score correlations were between .402 and .729 (p<0.001). CFA produced the factor loading values between .40 and .97, as well as GFI>.92, RMSEA<.80 and SRMR<.90. In the findings related to convergent validity, the standard regression weights was found to be (λ)>.50 and construct reliability coefficient (ω)> .70, and it was observed that the average variance explained in a factor was AVE > .50 and (ω) was greater than (AVE). Based on these values, it can be said that convergent validity was fulfilled. In discriminant validity, although ASV was smaller than AVE for all dimensions, it was found that MSV was greater than AVE only for F2 dimension and √AVE value was greater than correlations with other factors. The findings indicated that the scale partially fulfilled discriminant validity. As a result of all analysis related to validity, it was found that the five-factor construct concerning the original model was validated and the items and sub-dimensions were correlated to the scale and the items sufficiently explained the sub- dimension to which they are related. Based on all analysis conducted as part of the study, the Spiritual Care-Giving Scale was found to be a reliable and valid scale for the nurse group.
Validity and reliability of spiritual care-giving scale in nurse group
Keywords: Maneviyat; Manevi bakım; Güvenirlik; Geçerlik; Spirituality; Spiritual care; Reliability; Validity